PENGARUH PENGGUNAAN LULUR PEPAYA (Carica papaya L) TERHADAP KELEMBABAN KULIT TANGAN PADA WANITA USIA (47-50) TAHUN - Elma Catarina Davy; Nieke Andina Wijaya; Sri Usodoningtyas; Dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2025)
Outdoor activities that are exposed to sunlight for too long can cause water evaporation from the skin's surface to become rapid and reduce the natural moisture needed by the skin so that the skin becomes dry. Body scrub is a skin care product that functions to nourish, cleanse the body, and remove dead skin cells. Natural ingredients that can be used to make natural body scrubs are papaya fruit. Papaya contains the enzyme papain which has natural exfoliating properties and smoothes scaly skin texture. The purpose of this study was to determine the feasibility of papaya body scrub (Carica papaya L) reviewed from sensory tests and preference tests, to determine the effect of papaya body scrub (Carica papaya L) on hand skin moisture and to estimate the shelf life of papaya body scrub (Carica papaya L). This study used correlation analysis with a cross-sectional approach. The independent variable in this study was the use of papaya body scrub. The dependent variable was hand skin moisture in women aged (74-50 years) and the shelf life of the body scrub. Data collection using the observation method carried out by 30 women aged (74-50 years) and microbiological tests of shelf life. The data were analyzed by instrument test, basic assumption test and single ANOVA using SPSS Version 29 program. The results of the study were reviewed from the sensory test can be said to be feasible by obtaining the highest value of 19 while reviewed from the preference test obtained the highest value of 46, there is an effect of papaya scrub (Carica papaya L) on the skin after testing for 4 weeks with the results of the first week there were 3 respondents who had moist skin and in the fourth week there were 20 respondents who had moist skin and papaya scrub (Carica apaya L) could last until the 4th week. Keywords: Scrub, Papaya, Skin Moisture, Preference Level, Shelf Life